Approach via the XI rib of the right subphrenic space
It is planned indications about approaches to subfrenic lodge by way of XI rib in high posterior hydatic liver cysts or hepatic abces. Is important a previous and precise localisation of cyst and its posterior contact. An andtomical functional study of the thoraco abdominal region is made. distinguishing three sectors: interior ( of vertebra!dynamic), intermediate ( of respiratory dynamic) and externa